Disarm resistance: Fungal effectors target WAK alternative splicing variant for virulence - Liu, Zunyong; Jian, Yunqing; Shan, Libo (Cell reports (Cambridge), 2023)
Molecular interactions between pathogen effectors and plant immunity underpin the arms race of disease resistance and susceptibility. In a recently published Cell Reports paper, Zuo et al. reported the mechanistic characterization of Fusarium graminearum CFEM effectors that dampen ZmWAK17-mediated defenses in maize (Zea mays). Molecular interactions between pathogen effectors and plant immunity underpin the arms race of disease resistance and susceptibility. In a recently published Cell Reports paper, Zuo et al. reported the mechanistic characterization of Fusarium graminearum CFEM effectors that dampen ZmWAK17-mediated defenses in maize (Zea mays).